Peningkatan Kemampuan Membaca Al-Qur’an melalui Scientific Approach pada Pembelajaran Ilmu Tajwid di SD Insan Terpadu Sumberanyar Paiton Probolinggo - Musolli, Musolli; Makrufah, Makrufah (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2021)
This study discusses learning tajwid in improving the ability to read the Qur'an through a scientific approach at SD Insan Terpadu Sumberanyar Paiton. Learning tajwid is part of the procedure for reading the Qur'an, so that in its journey many methods or approaches are found in learning. One approach that can be used to strengthen the learning of tajwid is scientific learning, namely a learning approach which consists of activities; observing, questioning, associating, experimenting, and networking. This study uses a qualitative case study type method. The results of his research show that the Scientific Approach approach in the learning process of Tajweed Science at SD Insan Terpadu is very effective so that it can improve students' reading of the Qur'an and is very enjoyable. In addition, students are also able to master the material of recitation, gharib, and hadiths that they have learned.